2019
DOI: 10.2478/raft-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

The Issue of Leadership Styles in the Military Organization

Abstract: Enormously studied by specialists, the leadership of organizations is a primordial issue because the leader’s style conditions the efficiency of any social organization. This is one of the reasons why the current scientific concerns focus on studying the ways of improving leadership and the choice of leaders who have the skills and capabilities to successfully perform such functions. This paper deals with the characteristics of the military organization and the complex environment in which it operates, imposin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…It is thus interesting that despite the highly specific nature of this organizational context, trustful exchange relationships with peer leaders representing ethical role models whose behaviours emphasize fair treatment of and care about colleagues emerge as a relevant driver of military leaders' ethical behaviours. Moreover, the current findings demonstrate that peers' ethical behaviour and social exchange relationships with them outweigh the influence of upper leaders in influencing military leaders' EL (Stănciulescu & Beldiman, 2019). Yet, future research is needed to determine whether such pattern of findings is typical of the military context or can be generalized to other organizational settings.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It is thus interesting that despite the highly specific nature of this organizational context, trustful exchange relationships with peer leaders representing ethical role models whose behaviours emphasize fair treatment of and care about colleagues emerge as a relevant driver of military leaders' ethical behaviours. Moreover, the current findings demonstrate that peers' ethical behaviour and social exchange relationships with them outweigh the influence of upper leaders in influencing military leaders' EL (Stănciulescu & Beldiman, 2019). Yet, future research is needed to determine whether such pattern of findings is typical of the military context or can be generalized to other organizational settings.…”
Section: Discussionmentioning
confidence: 60%
“…Given such situations, military organizations are requiring effective leadership styles at all rank levels of military leaders under a pyramid‐shaped, strongly hierarchical structure (see for instance Moreno et al., 2021). In addition, military organizations have their own stratification system where all team leaders are promoted internally and entertain high social distance depending on their ranks (or job positions), that is, whether they are commissioned officers or non‐commissioned officers (Stănciulescu & Beldiman, 2019). Empirical research found that a large social distance between commissioned officers and non‐commissioned officers is negatively related to their ethical conduct (Stănciulescu & Beldiman, 2019).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…The leadership dimensions proposed in this study refer to the opinion of Hamad [9] who proposes two leadership styles to keep military organizations working optimally, namely transactional and transformational leadership styles. Stănciulescu & Beldiman [3] argue that in military organization, charismatic leadership style is still applied, while Mallick (2020) believes that in today's changing environment, military leaders should also be able to adopt effective and efficient thinking like it is on business decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital literacy of army's soldiers is very strategic to support military organizations in maintaining the resilience of the nation and society, so that the soldiers can help carry out analysis, verification and evaluation and support the delivery of correct information that does not disturb the public. Stanciulescu & Beldiman [3] also stated that the role of leaders in military organizations is very central in bringing organizations and soldiers to achieve their missions. In the digital era, the role of leaders is becoming increasingly central in facing intellectual, cultural and technological challenges as well as digital information systems that cause speed and access to communication with an unstoppable amount of data to overwhelm everyone in the organization.…”
Section: Introductionmentioning
confidence: 99%
“…Various constraints, due to the lack of human, financial and/or material resources, also manifest as challenges for the implementation of social innovation, which often demands substantial investment in training, technology and cultural change (Dyson, 2020; Sefidan et al, 2021). Successfully incorporating social innovation into military frameworks necessitates a nuanced understanding of these challenges, coupled with strategic planning and commitment (Stănciulescu, Beldiman, 2019). It is often advertised that social innovation will align seamlessly with the operational imperatives of military institutions, yet the promise of such change does not always look as promising (Micelli et al, 2023).…”
Section: Introductionmentioning
confidence: 99%